Analysis of Staffing Calculation Using the Workload Indicators of Staffing Need (WISN) Method in the Washing Unit of SPPG Wonosari - Rafly Fadel Muhammad; M. Trihudiyatmanto; Bahtiar Efendi (BIMA Journal (Business, Management, & Accounting Journal), 2026)
Purpose: This study aims to objectively analyse staffing requirements in the dishwashing unit of SPPG Wonosari using the Workload Indicators of Staffing Need (WISN) method based on actual workload conditions. Methodology: A case study design integrating quantitative WISN analysis was employed, with data collected through direct observation of work activities and in-depth interviews with dishwashing personnel and the kitchen supervisor. Results: The results show that the effective available working time was 2,144 hours or 128,640 minutes per worker per year. Based on the WISN calculation, the ideal staffing requirement was 18 workers, while only 16 were currently available, resulting in a WISN ratio of 0.9. Findings: This ratio indicates an understaffing condition that increases individual workload and may reduce operational efficiency and service quality. Novelty & Originality: This study provides empirical evidence on the application of the WISN method in a non-healthcare operational setting, specifically in a food service unit, which has received limited attention in prior research. Its originality emerges from the adaptation of a workforce planning tool traditionally used in healthcare to the context of institutional food service operations. Conclusions: The study concludes that the dishwashing unit at SPPG Wonosari requires additional staff to achieve optimal workload balance and maintain service quality. These findings offer practical insights for workforce planning in similar operational environments. Type of Paper: This paper is an empirical research paper.